Повышение качества экономического образования в Украине - Лернер, Юрий Ильич (НТУ "ХПИ", 2015)
Исследованы причины появления и углубления противоречий между изучением экономических дисциплин и реалиями экономической действительности. Разработаны рекомендации по уменьшению этих противоречий. Указанные рекомендации внедрены в практику преподавательской деятельности.

Reasons of appearance and deepening of contradictions are investigational between the study of economic disciplines and realities of economic reality. Recommendations are worked out on reduction of these contradictions. The indicated recommendations are inculcated in practice of teaching activity.
Upgrading of economic educations is in Ukraine
Keywords: противоречия; вуз; дисциплина; заблуждения экономического характера; contradictions; discipline; errors of economic character